Stability indicating LC method for estimation of Valbenazine and its degradation kinetic study. Issue 4 (24th February 2020) - Parmar, Payal J.; Patel, Vandana B.; Shah, Dimal A.
Abstract: Stability indicating analytical method helps to identify the instrinsic stability of molecule and likely degradation pathway. Present study involves development of a liquid chromatography method for Valbenazine which can be used in the analysis of forced degraded samples along with its degradation kinetic study. The liquid chromatography method was developed using Column (Shimadzu ODS Shim‐pack Solar (250* 4.6 mm, 5 µm)) as stationary phase and acetonitrile/water (90:10) was used as mobile phase. Flow rate was maintained at 1 mL/min and detection was performed using diode array detector at 210 nm. The retention time of Valbenazine Tosylate was observed to be 7.2 min. The linear regression analysis data for the calibration plots showed a good linear relationship for Valbenazine Tosylate over a concentration range of 1–20 µg/mL. The proposed method was validated with respect to linearity, accuracy, precision and robustness. To find out the possible degradation pathway, forced degradation studies were performed. The degraded product peaks were well resolved from the pure drug peak with significant difference in their retention time. To determine the order of reaction for base degradation, kinetic studies were performed. The drug was found to follow first order kinetic for base degradation condition. The developed method can be used for analysis of stability samples and routing quality control evaluation of Valbenazine Tosylate in bulk.